PECULIARITIES OF ANIMAL BEHAVIOR IN ZOOPHYSIOTHERAPY - Bilash , Yuliana (Collection of scientific papers «ΛΌГOΣ», 2025)
Animal behavior is a complex and multifaceted process that includes both instinctive and learned reactions to external and internal stimuli. Studying this behavior allows for a better understanding of the evolutionary mechanisms that shape the adaptation of animals to changing environmental conditions. Types of behavior, such as feeding, social, sexual, territorial, and defensive behaviors, can vary significantly depending on the species, age, and sex of the animal. Instincts, learning, interaction with other individuals, and the environment play a crucial role in determining how animals respond to external changes. An important aspect is also the study of behavioral disorders that may arise under the influence of stress or environmental changes. All these aspects are studied within the fields of zoology, ethology, and ecology, which helps develop a deeper understanding of animals' adaptive strategies.